Analisis Pengaruh Metode Taman Hujan dalam Menurunkan Debit dan Kekeruhan Air Limpasan Permukaan - Irfan Jufianto; Jazaul Ikhsan; Burhan Barid (Semesta Teknika, 2013)
The alteration in land use causes the loss of infiltration areas replaced by rigid pavement yet demand for groundwater is increasing thus unbalance in hydrology cycle occurred and water became the problem for human as the problem for this country nowadays. One of the solutions to keep the storage of groundwater is to make the rain garden in the area near the run-off sources. Nonetheless studied about rain garden only focus on the effect of pollution in the river and study about the impact of reducing run-off debit and turbidity has not been explored yet. Three infiltration models that had been used for this research were infiltration model with soil-only, rain garden, and the rain garden with infiltration hole. The results presented by the study were compared to get the efficient value from each infiltration model in reducing debit and turbidity in the unsaturated and saturated soil. The result of this study showed that the rain garden model with infiltration hole performed better result with unit time reliability for 3 minutes and higher efficiency value of 54.17% on unsaturated soil and 53.81% on saturated soil. It can also reduce the suspension in the surface run-off until 0 mg/l.